Facilitating Learning Online: Modeling the Skills for Reflective Practice - Judy Milton; Karen E. Watkins; Michelle D'Abundo; Barbara J. Daley (Adult Education Research Conference, 2004)
This study examined the interactions of facilitators in online reflective practice groups, focusing on the types of strategies used to convey these skills. Learners were found to use the skills modeled by the group facilitator, with the content of the interactions having a greater influence than facilitator style on learners’ use.